A GENDERED PERSPECTIVE ON POLICING VIOLENCE IN HAPPY VALLEY AND FARGO - Culpepper, T. Allen (Dialogue, 5(3), 2018)
Portrayal of a police officer determined to fight crime and execute justice in a harsh, isolated environment has become a television and film subgenre, often featuring women facing gender-related challenges. The issues raised in Sally Wainwright’s British television series Happy Valley, can be made more accessible, particularly to American undergraduate students, via its commonalities with the Coen brothers film Fargo. In both, a tough but compassionate policewoman pursues the more sociopathic of a pair of criminals involved in a botched kidnapping attempt instigated by an inept businessman, taking on the case for personal and professional honor, and as a responsibility to family and community. Catherine in Happy Valley and Marge in Fargo juggle “masculine” and “feminine” roles as they care for family members while policing violence. The women generally succeed in balancing their gender roles, whereas the men around them do not. But they sometimes assume the aggression associated with the male criminals they pursue. Happy Valley takes these issues deeper by giving Catherine a more intimate connection with one of the perpetrators and presenting the story more directly through a woman’s extra-patriarchal perspective, thus revealing the performative nature of gender roles and the limits of a patriarchal binary view of them. Looking at these issues in relation to Fargo paves the way for examination of their more complex and extensive treatment in Happy Valley. Keywords: television, women, gender, police officers, crime, northern England, film, violence, Happy Valley, detective, Fargo
Keywords: Type of access: Open Access